Effects of a short-term heat acclimation protocol in elite amateur boxers - Stone, B. L.; Ashley, J. D.; Skinner, R. M.; Polanco, J. P.; Walters, M. T.; Schilling, B. K.; Kellawan, J. M. (The Journal of Strength and Conditioning Research, 2022)
Boxing requires proficient technical and tactical skills coupled with high levels of physiological capacity. Although heat and humidity negatively affect acute exercise performance, short-term exercise training in hot and humid environments can lead to physiological adaptations that enhance exercise performance in both hot and thermoneutral conditions. In highly trained endurance athletes, exercise-induced acclimation can occur in as little as 5 days (known as short-term heat acclimation [STHA]). However, the impact of a 5-day heat acclimation (5-DayHA) in combat athletes, such as elite amateur boxers, is unknown. The aim of the present investigation was to determine whether a 5-DayHA improves aerobic performance in a thermoneutral environment and causes positive physiological adaptations in elite boxers. Seven elite amateur boxers underwent a 5-DayHA protocol, consisting of 60-minute exercise sessions in an environmental chamber at 32 °C and 70% relative humidity. Repeat sprint test (RST) evaluated aerobic performance in a thermoneutral environment 24 hours before and after the 5-DayHA. Presession and postsession hydration status (urine specific gravity) and body mass were assessed. After a 5-DayHA period, boxers significantly improved RST performance (13 ± 7 to 19 ± 7 sprints, d = 0.92, p = 0.03) but not pre-exercise hydration status (1.02 ± 0.01 to 1.01 ± 0.01, d = 0.82, p = 0.07). Therefore, these findings suggest 5-DayHA enhances aerobic performance in elite-level amateur boxers and may provide a viable training option for elite combat athletes.